Phosphorylation and dephosphorylation of the NarQ, NarX, and NarL proteins of the nitrate-dependent two-component regulatory system of Escherichia coli. - Schröder, I (1994)
The NarX, NarQ, and NarL proteins make up a nitrate-responsive regulatory system responsible for control of the anaerobic respiratory pathway genes in Escherichia coli, including nitrate reductase (narGHJI), dimethyl sulfoxide/trimethylamine-N-oxide reductase (dmsABC), and fumarate reductase (frdABCD) operons among others. The two membrane-bound proteins NarX and NarQ can independently sense the presence of nitrate and transfer this signal to the DNA-binding regulatory protein NarL, which controls gene expression by transcriptional activation or repression. To establish the role of protein phosphorylation in this process and to determine whether the NarX and NarQ proteins differ in their interaction with NarL, the cytoplasmic domains of NarX and NarQ were overproduced and purified. Both proteins were autophosphorylated in the presence of [gamma-32P]ATP and MgCl2 but not with [alpha-32P]ATP. Whereas these autophosphorylation reactions were unaffected by the presence of nitrate, molybdate, GTP, or AMP, ADP was an inhibitor. The phosphorylated forms of 'NarX and 'NarQ were stable for hours at room temperature. Each protein transferred its phosphoryl group to purified NarL protein, although 'NarQ-phosphate catalyzed the transfer reaction at an apparently much faster rate than did 'NarX-phosphate. In addition, NarL was autophosphorylated with acetyl phosphate but not with ATP as a substrate. NarL-phosphate remained phosphorylated for at least 3 h. However, addition of 'NarX resulted in rapid dephosphorylation of NarL-phosphate. In contrast, 'NarQ exhibited a much slower phosphatase activity with NarL-phosphate. These studies establish that the cytoplasmic domains of the two nitrate sensors 'NarX and 'NarQ differ in their ability to interact with NarL.